Anesthetic management of radical nephrectomy in patients with renal cell carcinoma involving renal vein or inferior vena cava. Issue 5 (October 2019) - Chen, Kun; Wang, Juan; Dai, Jinzhen; Luo, Ailin; Tian, Yuke; Guan, Zhonghui; Wang, Xueren
Objective: To investigate the perioperative anesthetic management of patients diagnosed with renal cell carcinoma (RCC) metastasized into the renal vein or inferior vena cava (IVC) after undergoing radical nephrectomy to provide clinical evidence for rational anesthetic interventions. Methods: A total of 81 patients with RCC extending into the renal vein or IVC, aged 17–73 years, undergoing radical nephrectomy were recruited. Preoperative status, intraoperative management, average operation time, average estimated blood loss, postanesthesia outcomes, and postoperative complications were retrospectively analyzed. Results: The mean operation time was 288 minutes (range 146–825 minutes). The mean estimated blood loss was recorded as 1905 mL (range 200–7000 mL). Among 81 cases, 9 patients (11.1%, 1 level II, 3 level III, and 5 level IV) were switched to undergo cardiopulmonary bypass. Significant hemodynamic fluctuations were observed in 39 patients who presented with level II–IV of tumor thrombus. One patient had pulmonary embolism and died of active cardiopulmonary resuscitation. The mean postoperative hospital stay was 12.8 days. Twenty-five cases with level III–IV tumor thrombus were transferred to the intensive care unit with endotracheal intubation due to massive intraoperative blood loss. The remaining 55 cases were transferred to the postanesthesia care unit 2 hours before being transferred to the ward. One patient had postoperative acute coronary syndrome and was discharged after effective interventions. Conclusion: Anesthetic management and intensive postoperative care play a pivotal role in the success of complete resection of RCC that metastasize into the IVC.